Human β-defensin 3 affects the activity of pro-inflammatory pathways associated with MyD88 and TRIF - Semple, Fiona (WILEY-VCH Verlag, 2011)
β-Defensins are cationic host defense peptides that form an amphipathic structure stabilized by three intramolecular disulfide bonds. They are key players in innate and adaptive immunity and have recently been shown to limit the production of pro-inflammatory cytokines in TLR4-stimulated macrophages. In the present study, we investigate the mechanism underlying the anti-inflammatory effect of human β-defensin 3 (hBD3). We show that the canonical structure of hBD3 is required for this immunosuppressive effect and that hBD3 rapidly associates with and enters macrophages. Examination of the global effect of hBD3 on transcription in TLR4-stimulated macrophages shows that hBD3 inhibits the transcription of pro-inflammatory genes. Among the altered genes there is significant enrichment of groups involved in the positive regulation of NF-κB including components of Toll-like receptor signaling pathways. We confirm these observations by showing corresponding decreases in protein levels of pro-inflammatory cytokines and cell surface molecules. In addition, we show that hBD3 reduces NF-κB signaling in cells transfected with MyD88 or TRIF and that hBD3 inhibits the TLR4 response in both MyD88- and TRIF-deficient macrophages. Taken together these findings suggest that the mechanism of hBD3 anti-inflammatory activity involves specific targeting of TLR signaling pathways resulting in transcriptional repression of pro-inflammatory genes.